Influence of Cu(СH[3]COO)[2] promoting additive on bituminous coal oxidation process; MATEC Web of Conferences; Vol. 194 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2018) - Bolgova D. Darya; Larionov K. B. Kirill Borisovich; Zenkov A. V. Andrey Viktorovich; Yankovsky S. A. Stanislav Aleksandrovich (Les Ulis, EDP Sciences, 2018)
Title screen